Targeting the OB-Folds of Replication Protein A with Small Molecules - Anciano Granadillo, Victor J.; Earley, Jennifer N.; Shuck, Sarah C.; Georgiadis, Millie M.; Fitch, Richard W.; Turchi, John J. (Journal of Nucleic Acids, 2010)
Replication protein A (RPA) is the main eukaryotic single-strand (ss) DNA-binding protein involved in DNA replication and repair. We have identified and developed two classes of small molecule inhibitors (SMIs) that show in vitro inhibition of the RPA-DNA interaction. We present further characterization of these SMIs with respect to their target binding, mechanism of action, and specificity. Both reversible and irreversible modes of inhibition are observed for the different classes of SMIs with one class found to specifically interact with DNA-binding domains A and B (DBD-A/B) of RPA. In comparison with other oligonucleotide/oligosaccharide binding-fold (OB-fold) containing ssDNA-binding proteins, one class of SMIs displayed specificity for the RPA protein. Together these data demonstrate that the specific targeting of a protein-DNA interaction can be exploited towards interrogating the cellular activity of RPA as well as increasing the efficacy of DNA-damaging chemotherapeutics used in cancer treatment.